2008
DOI: 10.1007/s10278-008-9112-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital Radiography Reject Analysis: Data Collection Methodology, Results, and Recommendations from an In-depth Investigation at Two Hospitals

Abstract: Reject analysis was performed on 288,000 computed radiography (CR) image records collected from a university hospital (UH) and a large community hospital (CH). Each record contains image information, such as body part and view position, exposure level, technologist identifier, and--if the image was rejected--the reason for rejection. Extensive database filtering was required to ensure the integrity of the reject-rate calculations. The reject rate for CR across all departments and across all exam types was 4.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 2 publications
(2 reference statements)
9
91
1
1
Order By: Relevance
“…Reject rates, which are defined as the total number of rejected images divided by the total number of images acquired over an established time period, are used by most clinical sites as an integral component of an overall QA program. Reject rates for sites using digital radiography systems are reported to range between 3 % and 10 % [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Reject rates, which are defined as the total number of rejected images divided by the total number of images acquired over an established time period, are used by most clinical sites as an integral component of an overall QA program. Reject rates for sites using digital radiography systems are reported to range between 3 % and 10 % [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, this retakes alone may not indicate overall improved image quality and optimal radiation dose. An acceptable level of contrast and brightness can be obtained through post-processing, even with a noisy image (Foos et al, 2009). It has been proposed that the two biggest quality errors in computed radiography (CR) are related to poor positioning and noisy images.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wu et al (2008), found that retakes with CR were similar to conventional filmscreen techniques; tumours ignored were sized 10-32mm, and 63% of the tumours were carcinomas. A reject analysis of 288.000 CR image records was published by Foos et al, 2009. Of these images collected from two large hospitals whereas chest exams were the most frequently performed examination at both institutions; positioning errors and anatomy cut-offs, followed by improper exposure were reasons for the most frequently occurring overall rejects.…”
Section: Errors In Film-screen Chest Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to identify outliers in practice allows for targeted interventions. There are examples of QC programs using automated collection methods to identify trends in computed tomography (CT), 14 , 15 and in CR tracking rejects and exposure levels over time 16 , 17 , 18 , 19 . AAPM Task Group 151 (6) discusses the appropriate quality assurance elements in a digital radiography program, including analysis of exposure levels.…”
Section: Introductionmentioning
confidence: 99%